Staying or Leaving? Investigating the Effects of Professional Development and Work-Life Balance on Turnover Intention in Chinese Private Universities - ChongFei, Shan; Aida Bt Samikon, Assoc. Prof Siti (Journal of Neonatal Surgery, 2025)
This study investigates the influence of professional development and work-life balance on turnover intention among young academic staff in Chinese private universities. Drawing on Organizational Equilibrium Theory and Herzberg’s Two-Factor Theory, the study employs a quantitative, correlational design using survey data from 287 early-career faculty members in Shijiazhuang, China. Structural equation modeling was used to test hypothesized relationships. Results indicate that professional development significantly and negatively affects turnover intention, affirming its role as a key motivator in faculty retention. Surprisingly, work-life balance was found to have a significant but positive effect on turnover intention, suggesting that even faculty with balanced lives may seek opportunities elsewhere if professional growth is lacking. These findings underscore the importance of an integrated institutional strategy that combines personal well-being with meaningful career development opportunities. The study contributes to both theory and practice by offering insights into the complex factors shaping turnover intention in a non-Western, private higher education context.